THE ROLE OF CUSTOMER SERVICE IN ENHANCING CUSTOMER VALUE AND FOSTERING CUSTOMER TRUST IN THE MODERN MARKET ENVIRONMENT IN BOGOR CITY - Ramadhan, Muhammad Asrul; Limakrisna, Nandan; Muharam, Hari (Yayasan Education and Social Center, 2025)
This study aims to investigate the role of customer service in enhancing customer value and fostering customer trust in the modern market environment of Bogor City. In an era of increasingly intense retail competition, customer service is a crucial factor in creating added value for customers and fostering sustainable trust. This study employs a qualitative approach, incorporating in-depth interviews and observations of consumers and modern market managers in Bogor City from October to December 2024. The study's findings indicate that the perception of customer value is significantly influenced by the quality of services, which is characterised as friendly, responsive, and instructive. High customer value then becomes a crucial foundation for growing customer trust, which in turn fosters customer loyalty and the sustainability of modern markets. However, there are challenges in the form of inconsistencies in service and limited human resources and market facilities that still require improvement. These findings emphasise the importance of standardised service management and staff training as primary strategies for enhancing service quality. The practical implications of this study are the need for continuous investment in training and facility development to strengthen the position of modern markets in Bogor City amidst retail market competition. This research is a significant contribution to the field of contemporary market management, as it aids in the development of effective service strategies that enhance customer value and establish long-term trust.